PENINGKATAN KAPASITAS SDM KARANG TARUNA “WISANGGENI” MELALUI PELATIHAN PEMBUATAN KONTEN MEDIA SOSIAL - Esti Margiyanti Utami; Santi Rahmawati; Qoharul Chikam; Panggih Perdana; Mahestya Andi Sanjaya (Politeknik Negeri Sriwijaya, 2023)
Karang Taruna is a forum for the younger generation to develop themselves, grow and develop on the basis of social awareness and responsibility from, by and for the younger generation, which is oriented towards achieving social welfare of the community. Karang Taruna is useful for advancing, developing and increasing productive activities by taking advantage of all the opportunities that exist in the environment, including human resources. The training activity for creating social media content as community service, which was carried out for Karang Taruna